Prediksi Intrusi Air Laut Berdasarkan Nilai Daya Hantar Listrik dan Total Dissolved Solid di Kabupaten Tangerang - Roh Santoso Budi Waspodo; Silvia Kusumarini; Vita Ayu Kusuma Dewi (The University of Lampung, 2019)
Intrusion of sea water is the infiltration of sea water into the soil. This might be caused by a groundwater excessive exploration. Tangerang District is one of the areas that have great potential sea water intrusion. The aim of research was to predict the limit of salt water intrusion based on the value of DHL and TDS. The primary data were measured using a TOA EC meter CM-14P and then were processed using Surfer 9.0 software and ArcGIS. The measurement results was compared with PAHIAA Decision (1986) and Carroll’s Classification (1962). The results showed that the intrusion area could be identified by DHL and TDS values. On the area located far from the beach, intrusion was influenced by the presence of a river in the region. This was indicated by the regression analysis that showed a correlation between distance and value DHL/TDS with a negative slope value. Based on DHL and TDS parameters in observation area, the groundwater conditions in Tangerang District within a radius of 0.095 km to 5 km from the littoral areas are categorized as medium intrusion zone (slightly brackish water) with DHL 1500-1999 μmhos/cm and TDS values 1000-3000 mg/LU.